Changes in liver stiffness measurements and fibrosis scores following sofosbuvir based treatment regimens without interferon. Issue 9 (September 2017) - Elsharkawy, Aisha; Alem, Shereen Abdel; Fouad, Rabab; El Raziky, Maissa; El Akel, Wafaa; Abdo, Mahmoud; Tantawi, Omnia; AbdAllah, Mohamed; Bourliere, Marc; Esmat, Gamal
Abstract: Background and Aim: Accurate evaluation of the degree of liver fibrosis in patients with chronic liver diseases is crucial, as liver fibrosis is important in order to make therapeutic decisions, determine prognosis of liver disease and to follow‐up disease progression. Multiple non‐invasive methods have been used successfully in the prediction of fibrosis; however, early changes in non‐invasive biomarkers of hepatic fibrosis under effective antiviral therapy are widely unknown. The aim of this study is to evaluate changes of transient elastography values as well as FIB‐4 and AST to platelet ratio index (APRI) in patients treated with Sofosbuvir‐based treatment regimen. Methods: This is a retrospective study including 337 chronic HCV Egyptian patients with genotype 4 mainly. They were treated with Sofosbuvir‐based treatment regimen. Transient elastography values were recorded as well as FIB‐4 and APRI were calculated at baseline and SVR12. Results: There was a significant improvement of platelets counts, ALT and AST levels, which in turn cause significant improvement in FIB‐4 and APRI scores at SVR12. Liver stiffness measurements were significantly lower in SVR12 (14.8 ± 10.7 vs 11.8 ± 8.8 kPa, P  = 0.000). About 77% of responders and 81.1% of cirrhotic patients showed improvement in liver stiffness measurements at SVR12.Univariate and multivariate regression analysis showed that failure to achieve improvement in liver stiffness measurements were significantly associated with relapsers and low baseline liver stiffness measurement. Conclusion: Sofosbuvir‐based treatment resulted in a clinically significant improvement in parameters of liver fibrosis.